Portfolio Manager Ownership and Mutual Fund Risk Taking - Ma, Linlin (Institutional Knowledge at Singapore Management University, 2014)
We study the effect of portfolio manager ownership, that is, “skin in the game”, on the risk taking of mutual funds. Using a holdings-based risk-shifting measure and a difference-indifferences approach, we find that managers with greater ownership engage in less risk-shifting behavior. We also find that managers with higher ownership exhibit superior reward-to-risk (i.e., Sharpe and appraisal) ratios. Funds with greater managerial ownership attract more capital flows. Taken together, our findings indicate that managerial ownership reduces managers’ incentive to engage in risk-shifting behavior and increases shareholder wealth.